Intermittent Sprinkler Irrigation for Establishment of Bare Root Strawberry Transplants - E. A. Golden; John R. Duval; Earl E. Albregts; C. M. Howard (EDIS, 2003)
Bare rooted strawberry transplants set in black polyethylene mulched beds are established by irrigating continuously for approximately 8 hours daily with overhead sprinklers for 10 to 14 days. Irrigation is provided to reduce the water stress caused by the damaged root system of the transplant, the high surface temperature of the black mulch, the high ambient air temperature, and dry weather condition usually present at time of transplanting. Without irrigation, transplants become defoliated; this results in considerable plant mortality and/or a delay in fruiting. Early yield is economically important in central Florida. This is document HS947, a publication of the Horticultural Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication Date: December 2003.